08.09: Design of cold‐formed steel composite flooring systems with partial shear connection. (13th September 2017) - Kyvelou, Pinelopi; Gardner, Leroy; Nethercot, David A.
ABSTRACT: Recently conducted research has shown that the development of composite action within systems comprising cold‐formed steel beams and wood‐based floorboards is feasible, leading to substantial improvements in structural performance. Based on the findings from a numerical investigation into the degree of interaction that may be achieved and the resulting benefits that may be obtained by treating the floor as a composite system, proposals for the design of such systems have been devised. At the core of the proposals is the calculation of the attained degree of shear connection and the shear bond coefficient of the system − as a function of the properties of its components and connectors – leading to accurate predictions of moment capacity and flexural stiffness. The method, which has been developed based on the fundamental concepts of current design methods employed in Eurocode 3, Eurocode 4 and Eurocode 5, provides practical and accurate design rules for cold‐formed steel composite floors, which are suitable for incorporation into future revisions of the Eurocodes.